“Thich Quang Duc” the monk of Thien Mu Temple - Makmool, Prachatip (Asian Journal of Traditional and Innovative Arts and Textiles, 2023)
The purpose of the scholarly article on "Thich Quang Duc" of Thien Mu Temple is to examine the historical background of the temple in Hue City, Vietnam. As well as researching Phra Thich Quang Duc's significance to Vietnamese Buddhism. Through gathering data through fieldwork, surveys, publications, internet media, non-participant observation, interviews, note-taking, photography, data analysis, and synthesis. According to the study's findings Buddhism, Taoism, and Confucianism were all brought to Vietnam from China and India. These days, Thian Mu Temple is a symbol of the demand for the right to practice Buddhism. Phra Thit Quang Duc was a prominent monk who killed himself by burning in order to demand justice for Buddhism. For Buddhism in Vietnam, this assertion is crucial. The first, religion, is still practiced and taught in Vietnam. The second is building and renovating temples for a variety of purposes, both secular and spiritual. The third phenomenon is the peaceful demand for rights. Lastly, the fact that he self-immolated became a major factor in the survival of Buddhism in Vietnam. "Bodhisattva Thich Quang Duc" was the moniker given to "Thich Quang Duc" Nowadays, Thien Mu Temple in Hue City, Vietnam, is a popular tourist destination. Even today, people still tell the stories of Thich Quang Duc and the building of Thien Mu Temple.